Aural Myiasis – A Case Report (Community Based Medical Journal, 2025)
Myiasis is a type of parasitosis caused by the larvae of diptera flies. Aural myiasis is the infestation of the external and or middle ear can be extremely dangerous if the larvae destroy the bone and penetrate into the brain. If the larvae penetrate the bone the fatality rate may be as high as 8%. Here we report a case aural myiasis in a patient with congenital mental retardation. He had complaints of complaints of severe earache, blood-stained discharge and something feeling of object left in his left ear over a week. On clinical examination, the right ear was found normal, while several active maggots and purulent secretion were found completely filling the left external auditory canal. 7 maggots were removed immediately after suction of purulent secretion. Then terpene oil was given in the left external auditory canal and another 25 maggots were removed under auto-endoscopic guidance. Later, the patient was treated with proper antibiotics, analgesic and antiallergic medication. Further management included assessment of hearing, computed tomography (CT) scan and follow up.  CBMJ 2025 January: Vol. 14 No. 01 P: 160-162